El liderazgo del director y el clima organizacional de la unidad de gestión educativa local de Ucayali - Contamana 2022 - Arriaga Tutusima, Hilario (2023)
The research had as general objective to determine the relationship between the leadership of the director and the organizational climate of the Local Educational Management Unit of Ucayali - Contamana 2022; opting for an applied type study with a non-experimental design; made up of a population of 71 workers, to whom the survey technique and the questionnaire were applied as an instrument for data collection; after processing the data in Excel and SPSS V.26. It is concluded that the leadership of the director is significantly related to the organizational climate contrasted by a coefficient of and a sig of (r=0.744; p=0.000). Likewise, the individual system dimension with a value of 0.590 and a sig of 0.000. The same for organizational system for a value of 0.695 and a sig of 0.000. For the interpersonal system, a coefficient of 0.468 and a bilateral sig of 0.000, both dimensions are significantly related to the leadership of the director.